A study on predictors of low birth weight - Reddy, Jillela Mahesh; Aravalli, Sasi Priya (International Journal of Contemporary Pediatrics, 2021)
Background: purpose of this study was to determine prevalence of maternal and social risk factors of low birth weight. The purpose of this study is to prevalence of maternal and social risk factors of low birth weight. Methods: The cross-sectional and comparative study was carried out by reviewing medical records of newborn delivered for one year in 250 newborn. Birth weight was categorized into two as low birth weight (birth weight <2500 grams), considered as cases, and normal birth weight (birth weight ≥2500 grams), considered as controls or the reference birth weight. Results: In our study mother’s age, socioeconomic, educational status, occupation as significant variables to be associated with low birth weight. caesarean section increased significantly with decrease in gestational age and maternal weight, history of abortion, iron supplementation Hypertension, anemia, and DM are Predictors of maternal and obstetric with low birth weight. Conclusions: Prompt identification of causes and prevention of premature delivery, proper knowledge of signs and symptoms of pregnancy complications, and preventing any physical trauma or its potential causes are recommended during pregnancy to prevent low birth weight.